Second glance: exploring consumer shifts to thrift shopping and perception of second-hand fashion - Nancy Ahmed Mobarak; Nada Ali Amin; Ahmed Abdel-Mohssen; Ahmed Sharif; Yasser Tawfik Halim; Karen Brickman (Future Business Journal)
Abstract Purpose The increasing consumer interest in second-hand fashion is reshaping the retail landscape, yet concerns about perceived risks and value continue to influence purchasing behaviors. While existing research highlights sustainability and affordability as key drivers of thrift shopping, the impact of perceived risks (functional and social) on customer switching behavior remains underexplored. This study examines how consumer perceptions of second-hand clothing influence their decision to switch from new to used fashion, integrating theories of perceived risk and customer switching behavior. By addressing this gap, the study contributes to a deeper understanding of the barriers and motivations behind second-hand clothing adoption. Design/methodology/approach This study employs a mixed-method approach to comprehensively analyze consumer switching behavior toward second-hand clothing. The qualitative phase includes in-depth interviews with an industry expert and 20 hand clothing consumers, providing nuanced insights into motivations and perceived barriers. The quantitative phase consists of an online survey with 290 respondents, statistically examining the relationships between perceived risks and switching behavior using correlation analysis and reliability testing. By integrating both qualitative and quantitative insights, this study ensures a holistic understanding of the factors influencing second-hand clothing adoption. Findings Analysis of the data using SPSS revealed that customers’ perceptions significantly affect their switching behavior concerning second-hand clothes. Originality/value This research contributes to the understanding of the dynamics between customer perception and market behavior in the context of second-hand clothing, highlighting the role of perceived risk in consumer decision-making processes.